Dimensions of Behavior of Green Product Using Organic Fertilizer (Qualitative and Countitative study of Farming Communities in Mulyoagung Village) - Alaik Muhammad, Syauqi; Djatmika, Ery Tri; Hermawan, Agus (Economics and Business Journal (ECBIS), 2023)
The purpose of this research is to analyze the direct and indirect relationship between green perceived quality, green perceived value, green perceived risk, green purchase intention, and green purchase behavior. This study examines the mediating role of green purchase intention in the relationship between the orientation of green perceived quality, green perceived value, green perceived risk, and green purchase behavior. This research is included in the mixed method research where both quantitative and qualitative are used. The research method used in this research is an unbalanced mixed method (concurrent embedded design) conducted on farmers in Mulyoagung Village. The research sample was taken using the quota sampling method with the sample size calculator as the method for determining the number of samples. Data collection was carried out online through a questionnaire form for 2 months on 219 farmers in Mulyoagung Village. Data analysis in this study used SEM-PLS assisted by SmartPLS 3.3.3 software. as well as for qualitative research using documentation and interviews. The results of the study show that there is a direct and indirect relationship between green perceived quality, green perceived value, green perceived risk, green purchase intention, and green purchase behavior. Not only that, there is a mediating role of green purchase intention in the relationship between the orientation of green perceived quality, green perceived value, green perceived risk, and green purchase behavior. This research is also supported by the qualitative results obtained from several predetermined informants. there is a mediating role of green purchase intention in the relationship between the orientation of green perceived quality, green perceived value, green perceived risk, and green purchase behavior. This research is also supported by the qualitative results obtained from several predetermined informants. there is a mediating role of green purchase intention in the relationship between the orientation of green perceived quality, green perceived value, green perceived risk, and green purchase behavior. This research is also supported by the qualitative results obtained from several predetermined informants).